Modulation of the expression of mimivirus-encoded translation-related genes in response to nutrient availability during Acanthamoeba castellanii infection - Silva, Lorena C. F.; Almeida, Gabriel M. F.; Assis, Felipe L.; Albarnaz, Jonas D.; Boratto, Paulo V. M.; Dornas, Fábio P.; Andrade, Ketyllen R.; La Scola, Bernard; Kroon, Erna G.; da Fonseca, Flávio G.; Abrahão, Jônatas S. (Frontiers in Microbiology, 2015)
The complexity of giant virus genomes is intriguing, especially the presence of genes encoding components of the protein translation machinery such as transfer RNAs and aminoacyl-tRNA-synthetases; these features are uncommon among other viruses. Although orthologs of these genes are codified by their hosts, one can hypothesize that having these translation-related genes might represent a gain of fitness during infection. Therefore, the aim of this study was to evaluate the expression of translation-related genes by mimivirus during infection of Acanthamoeba castellanii under different nutritional conditions. In silico analysis of amino acid usage revealed remarkable differences between the mimivirus isolates and the A. castellanii host. Relative expression analysis by quantitative PCR revealed that mimivirus was able to modulate the expression of eight viral translation-related genes according to the amoebal growth condition, with a higher induction of gene expression under starvation. Some mimivirus isolates presented differences in translation-related gene expression; notably, polymorphisms in the promoter regions correlated with these differences. Two mimivirus isolates did not encode the tryptophanyl-tRNA synthetase in their genomes, which may be linked with low conservation pressure based on amino acid usage analysis. Taken together, our data suggest that mimivirus can modulate the expression of translation-related genes in response to nutrient availability in the host cell, allowing the mimivirus to adapt to different hosts growing under different nutritional conditions.